One‐Step Synthesis of N‐doped Graphene Quantum Sheets from Monolayer Graphene by Nitrogen Plasma. (24th March 2014) - Moon, Joonhee; An, Junghyun; Sim, Uk; Cho, Sung‐Pyo; Kang, Jin Hyoun; Chung, Chul; Seo, Jung‐Hye; Lee, Jouhahn; Nam, Ki Tae; Hong, Byung Hee
<x xml:space="preserve">Abstract</x> High‐quality N‐doped graphene quantum sheets are successfully fabricated from as‐grown monolayer graphene on Cu using nitrogen plasma, which can be transferred as a film‐like layer or easily dispersed in an organic solvent for further optoelectronic or photoelectrochemical applications. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>